Pengaruh Digital Marketing terhadap Keputusan Pembelian dan Kepuasan Pelanggan pada Jasa Online Travel Agent - Didit Iswahyuniarto (Syntax Corporation Indonesia, 2023)
The purpose of this study is to determine the influence of digital marketing strategies on Online. Travel Agents on purchasing decisions based on the AISAS method and its implications for customer satisfaction. Online Travel Agent (OTA) is a website that sells travel products and services through digital marketing to customers. These OTA products include hotels, flights, travel packages, and car rentals. OTAs here are third parties that resell services on behalf of other businesses. This study used descriptive statistical data analysis method. The presentation of descriptive statistical data is usually done in the form of graphs or tables. Descriptive statistics include mean, maximum, minimum, and standard deviation. Digital Marketing OTA expressed in (X) has a strong correlation with the dependent variable: Purchase Decision expressed in (Y1) which has an index correlation of 0.663 or 66.3%. The correlation of the influence of the Purchase. Decision variable (Y1) on the Customer Satisfaction variable (Y2) is significant because it has an index correlation of 0.633 or 63.3%, so it is stated that the correlation of the Y1 variable to the Y2 variable is strong. This research concludes that customers decide to purchase OTA products after verifying that certainty about the benefits in transactions such as prices, promotions and reservation fees are in line with expectations. Certainty of benefits and convenience when transacting based on information successfully tracked on the OTA website is the reason customers make purchasing decisions. Product purchase transactions at selected Online Travel Agents (OTA) in terms of price, promotions and facilities are very profitable and customers are satisfied because their expectations have been met. The ease of accessing information about the benefits, benefits and transaction prices facilitated by the customer's preferred OTA digital marketing service has met his expectations.